Teologi Hikmat dalam Kitab 2 Tawarikh (International Forum of Researchers and Lecturers, 2024)
Thei purposei ofi thisi articlei isi toi explorei thei meaningi andi theologyi ofi wisdomi ini thei booki ofi 2i Chronicles.i Thei methodi usedi ini writingi thisi articlei isi ai deductive,i qualitativei researchi approach,i withi datai collectioni conductedi throughi Libraryi Researchi methods,i includingi journals.i Thei theologyi ofi wisdomi ini 2i Chroniclesi highlightsi wisdomi (חָכְמָה/khokmah)i asi ai centrali themei thati integratesi intellectual,i practical,i andi spirituali dimensions.i Wisdomi isi noti limitedi toi theoreticali intelligencei buti alsoi encompassesi tangiblei abilitiesi toi overcomei challenges,i lead,i andi build.i Ini thei contexti ofi thisi book,i wisdomi isi regardedi asi ai divinei gifti rootedi ini thei feari ofi thei Lord,i asi illustratedi ini thei storyi ofi Solomoni (2i Chr.i 1:7-12).i Solomoni prayedi fori wisdomi toi leadi Israel,i emphasizingi wisdomi asi ai gifti thati enablesi fairi andi prudenti decision-making.i Wisdomi ini thisi booki isi dividedi intoi twoi types:i speculative,i whichi includesi reflectioni oni humani existence,i andi didactic,i whichi isi practicali andi instructional,i suchi asi proverbsi thati guidei dailyi life.i Wisdomi isi characterizedi byi universal,i practical,i ethical,i andi religiousi traits,i reflectingi itsi connectioni toi morali valuesi andi ai relationshipi withi God.i Ini 2i Chronicles,i wisdomi isi manifestedi ini aspectsi ofi leadershipi (2i Chr.i 1:10),i thei constructioni ofi thei Templei (2i Chr.i 2:12),i andi thei regulationi ofi worshipi (2i Chr.i 7:14).i Thisi wisdomi underscoresi thei importancei ofi obediencei toi Godi asi thei sourcei ofi wisdom,i guidingi decisionsi andi buildingi thei livesi ofi thei peoplei ini righteousness.